Lower Extremity Skeletal Muscle Mass, but Not Upper Extremity Skeletal Muscle Mass, Is Inversely Associated with Hospitalization in Patients with Type 2 Diabetes - Hidetaka Hamasaki (Journal of Diabetes Research)
Aim. To investigate the association of skeletal muscle mass with metabolic parameters and hospitalization in patients with type 2 diabetes. Methods. A retrospective observational study was conducted in patients with type 2 diabetes between May 2013 and November 2015. Body composition was measured by bioelectrical impedance analysis. Multiple regression analysis was performed to identify the association between skeletal muscle mass and metabolic parameters. Cox proportional hazard analysis was performed to assess the association between skeletal muscle mass and hospitalization. Results. A total of 121 patients were enrolled in this study. The mean age of patients was 59.4 ± 14.2 years. During a mean follow-up of 730 ± 253 days, three patients (2.8%) died and 79 patients (65.3%) were admitted to our hospital. After adjustment for age, sex, height, and weight, it was found that lower extremity skeletal muscle mass (LSM) was inversely associated with brachial-ankle pulse wave velocity (β=−0.108, P=0.008). Moreover, LSM was significantly associated with reduced risk of hospitalization (hazard ratio = 0.752; 95% confidence interval, 0.601–0.942; P=0.013). In contrast, upper extremity skeletal muscle mass (USM) did not exhibit any significant association. Conclusion. LSM, but not USM, is important for managing patients with type 2 diabetes. This trial is registered with UMIN000023010.